ETNOBOTANI TUMBUHAN OBAT OLEH WARGA DAYAK MERATUS DI DESA GUNUNG RIUT KABUPATEN BALANGAN KALSEL - Nashrul Wathan; Rina Rina; Nadia Rahmah; Hilya Aulia; Nita Pujianti (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
Traditional knowledge about the use of medicinal plants owned by various indigenous Dayak tribes in Kalimantan reflects that people's lives cannot be separated from the surrounding natural resources, especially medicinal plants. The purpose of this study was to determine the types of medicinal plants, the percentage of medicinal plant parts used and to determine how to process and use medicinal plants by traditional healers of the Dayak Meratus tribe in Gunung Riut Village. Informants are determined by purposive sampling technique. The result of the interview showed 28 species and divided into 18 families of medical plants used to treat toothache, back pain, skin diseases, fever, influenza, syphilis, fractures, wounds, hypertention, jaundice, malaria, hemorrhoids, increase stamina, laxative, asthma and indigestion. The percentage of plant parts that are widely used are leaves (26.67%), roots (23.33%), and stems (13.33%). Processing methods by soaking, boiling, pounding, without processing, squeezing, heating, cutting and burning. How to use by applying, massaging, sticking, drinking, pinching, bathing, and eating.